Crowd monitoring and detection - Li, Xin (Nanyang Technological University, 2022)
Covid-19 has impacted our life a lot ever since the virus emerged in early 2020. Due to its rapid spreading characteristics, several safety measures have been put into service for safe management. Singapore has implemented various laws and regulations regarding social gatherings, mask-wearing, safe distancing, etc.